2021
DOI: 10.1002/ange.202101994
|View full text |Cite
|
Sign up to set email alerts
|

Force‐Induced Turn‐On Persistent Room‐Temperature Phosphorescence in Purely Organic Luminogen

Abstract: Research of purely organic room‐temperature phosphorescence (RTP) materials has been a hot topic, especially for those with stimulus response character. Herein, an abnormal stimulus‐responsive RTP effect is reported, in which, purely organic luminogen of Czs‐ph‐3F shows turn‐on persistent phosphorescence under grinding. Careful analyses of experimental results, coupled with the theoretical calculations, show that the transition of molecular conformation from quasi‐axial to quasi‐equatorial of the phenothiazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The introduction of a conformation variable moiety into chromophores is an efficient strategy to design dynamic materials, which may generate multiple thermodynamically metastable states through conformational change under external stimuli. [19][20][21] In fact, a variety of smart luminescent materials have been achieved by Minakata, 22 Li 23 and Xu 24 by virtue of saddle-shaped phenothiazine building blocks bearing two distinct quasi-axial and quasi-equatorial conformers. However, conformation flexible chromophores are still limited and underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a conformation variable moiety into chromophores is an efficient strategy to design dynamic materials, which may generate multiple thermodynamically metastable states through conformational change under external stimuli. [19][20][21] In fact, a variety of smart luminescent materials have been achieved by Minakata, 22 Li 23 and Xu 24 by virtue of saddle-shaped phenothiazine building blocks bearing two distinct quasi-axial and quasi-equatorial conformers. However, conformation flexible chromophores are still limited and underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…For these target compounds, the 1,2,3-trifluorophenyl group was introduced to all of them to strengthen the intermolecular hydrogen bonding and inhibit the non-radiative transition, while the substituents in the 2-position of the phenothiazine 5,5-dioxide group were changed from each other, with the aim to accurately adjust the molecular packing and investigate the structure–packing–RTP property relationship. 26–28…”
Section: Introductionmentioning
confidence: 99%
“…was introduced to all of them to strengthen the intermolecular hydrogen bonding and inhibit the non-radiative transition, while the substituents in the 2-position of the phenothiazine 5,5-dioxide group were changed from each other, with the aim to accurately adjust the molecular packing and investigate the structure-packing-RTP property relationship. [26][27][28] Excitingly, accompanying the adjustment of the substituent groups on the 2-position of the phenothiazine 5,5-dioxide ring from the methoxyl group to a bromine atom, and then to hydrogen, fluorine and chlorine atoms, the RTP lifetimes in crystals of the corresponding luminogens increased from 144 ms (PTZO-CH 3 O) and 179 ms (PTZO-Br) to 332 ms (PTZO-H), and then to 446 ms (PTZO-F) and 745 ms (PTZO-Cl). Single crystal analyses indicated that the minor differences in the substituents could lead to much different intermolecular p-p interactions, thus resulting in the changed RTP properties.…”
Section: Introductionmentioning
confidence: 99%